Meteorological data in the simulation of combined system work conditions = Dane meteorologiczne w symulacji warunków pracy ogólnospławnej sieci kanalizacyjnej - Wira, Jerzy; Nowogoński, Ireneusz; Ogiołda, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the paper results of combined system work simulation basing on rainfall data were shown. Rainfall height values were read for three time interval precisions: 10, 30 and 60 minutes. The last event corresponds with precision gained when using pluviographical specification.
Keywords: ogólnospławna sieć kanalizacyjna; sieć kanalizacyjna; opady; wysokość opadów; combined sewage system; rainfall-runoff phenomena; simulation